The role of nitrogen fixation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Nitrogen fixation in tropical cropping systems by Ken Giller end Kate Wilson 1991 313pp ISBN 085198 6714 Hbk CABI, Wallingford Oxon OX10 ODE, UK